2022
DOI: 10.3390/nu14101998
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin D in COVID-19 Patients Is Not Related to Inflammatory Markers and Patients’ Outcomes—A Single-Center Experience and a Brief Review of the Literature

Abstract: The aim of the study was to evaluate the vitamin D status in hospitalized COVID-19 patients and the correlation with C reactive protein (CRP), ferritin, fibrinogen, and peripheral blood leukocytes, as well as inflammatory derived indices. A prospective study was performed on 203 COVID-19 hospitalized patients, classified by disease severity. Blood was collected after admission, and inflammatory biomarkers and vitamin D status were assessed using routine laboratory procedures. No significant correlation was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…This topic was further addressed by Citu et al in 2022, and it was found that the neutrophil to leukocytes ratio (NLR), derived neutrophil to leukocytes ratio (dNLR), and monocyte to leukocytes ratio (MLR) were found to be good predictors of severity and mortality in patients with COVID-19, with a hazard ratio (HR) of 3.85, 6.4, and 3.05, respectively, on univariate Cox regression [111]. This is corroborated by Cocos et al, Hutanu et al, Todor et al Restea et al [26,29,36,48]. From this point of view, similar changes could be observed in pediatric cases [22,23,30,39,112].…”
Section: Complete Blood Counts (Cbc) and Other Blood Test Markersmentioning
confidence: 68%
See 1 more Smart Citation
“…This topic was further addressed by Citu et al in 2022, and it was found that the neutrophil to leukocytes ratio (NLR), derived neutrophil to leukocytes ratio (dNLR), and monocyte to leukocytes ratio (MLR) were found to be good predictors of severity and mortality in patients with COVID-19, with a hazard ratio (HR) of 3.85, 6.4, and 3.05, respectively, on univariate Cox regression [111]. This is corroborated by Cocos et al, Hutanu et al, Todor et al Restea et al [26,29,36,48]. From this point of view, similar changes could be observed in pediatric cases [22,23,30,39,112].…”
Section: Complete Blood Counts (Cbc) and Other Blood Test Markersmentioning
confidence: 68%
“…The major laboratory markers that were studied by Romanian authors are displayed in Table 1. Yes, even more so in Roma [53,54,[58][59][60][61][62]70] Diabetes [48,94] Antiphospholipid syndrome [47] Hypertension [27] Cardiac dysfunction [46,73,93] Overweight/metabolic syndrome [27,54,93] Lung involvement [50,57] PIMS [83] Chronic Spontaneous Urticaria Exacerbation [42] Pneumothorax/ pneumomediastinum [31,72] Liver failure [44] Multiple organ dysfunction [ [57,58,102,103] No [55] More comorbidities [29,101] Lung involvement [57] In addition, this article aimed to identify gaps in this research and provide encouragement for Romanian research to focus on novel and detailed aspects of the pandemic. For instance, as Romania grapples with the aftermath of the COVID-19 pandemic, understanding the long-term effects of the disease is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ozturk et al 24 found no significant relation between vitamin D levels and covid-19 severity nor with the other inflammatory markers. Of note, the study of Huțanu et al 25 concluded that low vitamin D levels are related to more severe forms of the disease but not with inflammatory markers or mortality. Also, the study of Bogliolo et al 26 failed to document a relation between vitamin D levels and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The article by Hut , anu et al [1] attempts to evaluate the protective effects, or lack thereof, provided by serum vitamin D against COVID-19.…”
mentioning
confidence: 99%